How weird is it? : A freaky book all about strangeness. - Hillman, Ben (New York : Scholastic, 2009)
Strange but fascinating facts about everyday things that turns out to be extraordinary.
Mummy kitty -- Sleepy bacteria -- Swimming in comets -- Fungus is family -- Bird magnet -- Neanderthal -- Superposition --Anglefish in love -- Dark energy -- Scorpions? gross! pizza? barf! -- Find the octopus -- Neutron star -- Martians -- Gigantic jets ; Rocky Mountain locust plague -- Surinam toad babies -- Liquid nitrogen -- Water bear -- Hollow Earth theory -- Neutrinos -- Cosmic static -- X-ray sun.
Keywords: Science --Miscellanea --Juvenile literature; Science --Miscellanea.